Managing culture in organization - Yusof, Ab. Aziz; Ali, Juhary (Universiti Utara Malaysia, 2000)
Almost all organizations claim to have their own organizational culture. Organizational culture plays significant roles in influencing members in organizations in terms of commitment, loyalty and satisfaction. Organizations do not only produce products or services to be marketed, but they also produce organizational values, symbols and norms to be delivered, promoted, extended and appreciated to existing members, newcomers and outsiders. The organizational culture is not only able to change, guide and display the behaviour of the individual but also give significant contributions by influencing the thought, feeling, interacting and performance in the organization.